Engineering geology : rock in engineering construction - Goodman, Richard E. (New York : John Wiley and Sons, 1993)
This book is about: Geology; Geologic investigations; Shales, Sandstones, and associated rocks; Soluble rocks; Plutonic igneous rocks; ...
Keywords: Engineering; Rock mechanics; Engineering geology; Rock mechanics